Implementation of Equal Distribution of Education for Indonesia’s Disadvantaged, Frontier, and Outermost Regions - Nurfadilah, Amelia; Ash-Shidiq, Ali Umar; Sukma, Adinda; Mardiansyah, Andri; Lestari, Anisa Pauji; Rahmah, Winni Rizqi; Sonya, Endah Ratna (FISIP UIN SGD Bandung, 2024)
Two important dimensions of education in Indonesia which have often been a problem so far are the problem of widespread access to education and equality of education in Indonesia. These two problems are still a polemic in educational development in Indonesia. Many factors influence the implementation and distribution of education. Expansion is characterized by the ease with which society (citizens) can obtain education, while educational equality is a situation that is the same between the implementation of education carried out in both cities and villages. Through the literature, researchers looked at the implementation of educational equality in Indonesia, so it was found that the government was trying to provide rights based on UU No. 20 of 2003 through the educational equality program in the 3T area, so it was known that the initial explanation regarding this implementation was presented in the discourse on the importance of educational equality, then the basis The basis of the education equality policy was to look at the problems and also the quality of education itself. Afterwards, it was found that policies related to education equality had been implemented by the government through the 3T teaching undergraduate program and the realization of other programs which were considered to have an influence on the progress of education in Indonesia.